Generative AI in Educational Research: Opportunities, Integrity Risks, Ethical Challenges: A Prisma Guided Systematic Review - Kusumawati Shindi Nur Rahmawati; Oktaviani Adhi Suciptaningsih; Ade Eka Anggraini (Papanda Publisher, 2026)
This study systematically examines the opportunities, academic integrity risks, and ethical challenges associated with the use of Generative Artificial Intelligence (GenAI) in educational research. A PRISMA guided systematic literature review was conducted using five major databases: SpringerLink, ScienceDirect, Taylor & Francis, Emerald, and MDPI covering publications from 2020 to 2025. A total of 28 peer-reviewed articles met the inclusion criteria and were analyzed through thematic synthesis and bibliometric mapping using VOSviewer. The findings identify three dominant themes: (1) research opportunities, where GenAI enhances literature exploration, academic writing, and analytical efficiency; (2) risks to academic integrity, including AI-assisted plagiarism, ghostwriting, and reduced critical reflection; and (3) the growing need for ethical frameworks and AI literacy emphasizing responsibility, transparency, and accountability in research practices. Bibliometric results reveal an increasing concentration of high-impact (Q1–Q2) publications and expanding international collaboration on AI ethics in education. Theoretically, this study adopts an axioetic approach, understood as the integration of epistemic knowledge and moral values, to interpret ethical tensions arising from GenAI use in research. Practically, the findings provide guidance for researchers, higher education institutions, and policymakers in developing ethical guidelines, strengthening AI literacy, and promoting transparent research standards. Overall, GenAI should be positioned as a reflective research partner rather than a substitute for human intellectual and ethical responsibility.